University of the Philippines Mindanao Interactive Learning Center a proposed strategy - Fedillaga, Albert Joseph A. (School of Management, University of the Philippines Mindanao, 2007)
The Interactive Learning Center (ILC) of the University of the Philippines Mindanao has recently been split from another organization of the university. This enabled the ILC to define more precisely and pursue its mandate and functions. Personal communication, interviews and perusal of official documents were made to provide an analysis of the internal factors that drive the organization?s processes. External factors that may affect the organization are also scanned and analyzed. Eventually, a strategy that involves the increase of the organization?s visibility to its constituents and the improvement of its facilities was formulated. This strategy may eventually lead to the creation and promotion of multimedia interactive learning materials and the fulfillment of the mandate of the ILC. To support this strategy, programs that will financially sustain the organization are proposed.